Artificial intelligence in food biotechnology: trends and perspectives - Amore, Antonella; Philip, Sheryl (Frontiers in Industrial Microbiology, 2023)
Artificial Intelligence (AI) is the creation of intelligent systems able to execute specific tasks which would normally need human intelligence to function. Today, AI is widely used to assist research and development in industrial biotechnology. Many biotech firms rely on AI tools. The food industry is among the industrial sectors where AI has only recently been explored. AI enhances food biotechnology by supporting food enzymes engineering, microbial metabolic engineering, food safety and, in general, food microbiology. The use of AI tools in the food industry ranges from food processing – including all aspects of the production of food ingredients – to food quality and safety. This paper highlights the emerging importance of AI in some specific sectors of food biotechnology: development of new process-aid enzymes, precision fermentation, food safety and toxicity, food microbiology, and the study of the interplay between food and gut microbiome. These represent only a few examples of the myriad of applications that AI is seeing and will see in the food biotech sector. This Perspective paper intends to stimulate the discussion around the intricate relationship between AI and such research topics.